1999
DOI: 10.2527/1999.7792336x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the ovine callipyge locus: III. genotypic effects on meat quality traits.

Abstract: ABSTRACT:A resource flock of 362 F 2 lambs provided phenotypic and genotypic data to estimate effects of callipyge ( CLPG) genotypes (NN, NC, CN, and CC) on meat quality traits. The mutant allele is represented as C, the normal allele(s) as N, and the paternal allele of a genotype is given first. Lambs of each genotype born in 1994 and 1995 were serially slaughtered in six groups at 3-wk intervals starting at 23 wk of age. Warner-Bratzler shear force and subjective evaluation of marbling were collected during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 26 publications
1
27
0
Order By: Relevance
“…Dramatic effects on muscle development, carcass composition, shape, and meat quality are hallmarks of the callipyge syndrome (Koohmaraie et al 1995;Freking et al 1998bFreking et al , 1999. The muscle hypertrophy phenotype is expressed in a unique parent of origin-dependent manner referred to as paternal polar overdominance (Cockett et al 1996;Freking et al 1998a).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Dramatic effects on muscle development, carcass composition, shape, and meat quality are hallmarks of the callipyge syndrome (Koohmaraie et al 1995;Freking et al 1998bFreking et al , 1999. The muscle hypertrophy phenotype is expressed in a unique parent of origin-dependent manner referred to as paternal polar overdominance (Cockett et al 1996;Freking et al 1998a).…”
mentioning
confidence: 99%
“…The only genotype that expresses muscle hypertrophy in this type of gene action is one in which the mutant callipyge allele (C) is inherited from the sire and a normal allele (N) from the dam (genotype CN). Interestingly, sheep with two copies of the mutant allele (genotype CC) did not express muscle hypertrophy even though other phenotypes such as increased longissimus muscle calpastatin enzyme activity and increased longissimus muscle shear force were observed relative to noncarrier (genotype NN) or maternal-derived heterozygous (genotype NC) genotypes (Freking et al 1999). Understanding the mechanism by which the CLPG mutation alters these phenotypes would improve our basic knowledge of factors involved in muscle growth, carcass leanness, and meat quality, as well as delineate unique forms of genomic imprinting regulation.…”
mentioning
confidence: 99%
“…It was shown to be inherited and fully controlled by an autosomal locus (clpg) mapping to the telomeric end of sheep chromosome 18 (Cockett et al 1994;Freking et al 1998c). Subsequent marker-assisted segregation analysis revealed that the callipyge phenotype is subject to a unique parent-oforigin effect, referred to as polar overdominance, in which only heterozygous individuals having inherited the CLPG mutation from their sire express the muscular hypertrophy .…”
mentioning
confidence: 99%
“…any animal inheriting the Callipyge allele from its dam does not display the phenotype) (Cockett et al, 1996). The effect on meat quality is large; animals expressing the Callipyge phenotype have remarkably tough meat as assessed through shear-force measures or sensory panels, and the meat is associated with high calpastatin levels (Freking et al, 1999;Duckett et al, 2000). Fine mapping of the Callipyge locus, and its impact on associated imprinted genes was described by Charlier et al (2001), leading to the identification of the causative mutation (Freking et al, 2002).…”
Section: Genes Impacting On Meat Qualitymentioning
confidence: 97%